Evaluation of electroencephalographic changes in patients with the new onset suspicious seizure movements - Fattahzadeh, Ghasem; Atalu, Abolfazl; Hamed, Zahra; Abdolzadeh, Anahita (International Surgery Journal, 2021)
Background: Abnormal EEG is a predictor of seizure relapse. Obtaining data related to the diagnosis and outcome of the first seizures is necessary for improving care for these patients, whereas data for these studies is scarce and is limited to a few a few centres. The aim was evaluation of the EEG changes in patients with first suspicious movements of seizure. Methods: All of the patients with first suspicious movements of seizure referred to Alavi hospital of Ardabil from March 2019 to March 2020 enrolled in this study. Data including age, gender, etiology of the seizure, seizure type and EEG changes gathered. Collected data were analyzed by statistical methods in SPSS version 21. Results: 71 patients were studied. Based on the seizure type, 50 (70.4%) patients had motor, 10 (14.1%) patients had nonmotor and 11 (15.5%) patients had focal seizures type impaired awareness. EEG findings were normal in 46 patients (64.8%). There were slowing waves and epileptic discharge in 12 (16.9%) and 13 (18.3%) patients, respectively. Abnormal EEGs recorded in routine modality in 16 patients (64%), H. V. modality in 2 patients (8%), Ph. S. modality in 2 patients (8%) and both routine and excitatory modalities in 5 (20%) patients. Conclusions: There was not a significant relationship between EEG findings and age, gender, seizure etiology and seizure type. Also there was not a significant relationship between abnormal waves in different modalities and type and etiology of the seizures.